Optical spin-transfer-torque-driven domain-wall motion in a ferromagnetic semiconductor - Ramsay, A.J.; Roy, P.E.; Haigh, J.A.; Otxoa, R.M.; Irvine, A.C.; Janda, T.; Campion, R.P.; Gallagher, B.L.; Wunderlich, J. (American Physical Society, 2015)
We demonstrate optical manipulation of the position of a domain wall in a dilute magnetic semiconductor,GaMnAsP. Two main contributions are identified. First, photocarrier spin exerts a spin-transfer torque on the magnetization via the exchange interaction. The direction of the domain-wall motion can be controlled using the helicity of the laser. Second, the domain wall is attracted to the hot spot generated by the focused laser. Unlike magnetic-field-driven domain-wall depinning, these mechanisms directly drive domain-wall motion, providing an optical tweezerlike ability to position and locally probe domain walls.